2004
DOI: 10.1016/j.jasms.2003.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable amine-TFA self assembly

Abstract: Supramolecular assemblies that are formed between amines and trifluoroacetic acid were studied using electrospray ionization mass spectrometry. Distinctive association behavior of primary, secondary, and tertiary amines with trifluoroacetic acid upon identical experimental conditions is observed and indicates that steric effects dominate in the formation of these protonated clusters. Extraordinary complexation behavior is observed in the case of RϪ(ϩ)-␣-methylbenzylamine and 4-tert-butyl-cyclohexylamine that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…H‐bond phosphate clustering or salt bridging between phosphate and secondary amino groups are both possible events . Most likely, the indefinite linear growth of PAs‐phosphate modules is prevented by the entropy‐driven cyclization that confers additional stability to the aggregates, in analogy to the supramolecular self‐assemblies of primary, secondary and tertiary amines with trifluroacetic acid (TFA) . In this latter case, density functional theory calculations combined with ESI MS data indicated that the prevalent [M 4 TFA 3 + H] + clusters (M stands for an amine molecule) are stabilized by a macrocyclic arrangement.…”
Section: Resultsmentioning
confidence: 97%
“…H‐bond phosphate clustering or salt bridging between phosphate and secondary amino groups are both possible events . Most likely, the indefinite linear growth of PAs‐phosphate modules is prevented by the entropy‐driven cyclization that confers additional stability to the aggregates, in analogy to the supramolecular self‐assemblies of primary, secondary and tertiary amines with trifluroacetic acid (TFA) . In this latter case, density functional theory calculations combined with ESI MS data indicated that the prevalent [M 4 TFA 3 + H] + clusters (M stands for an amine molecule) are stabilized by a macrocyclic arrangement.…”
Section: Resultsmentioning
confidence: 97%
“…As well as the main peaks corresponding to the free cations, the ESI-MS spectra (not reported) show peaks due to ion aggregates formed by two cations and the related anion [(M + ) 2 •Y -], that easily reveal the nature of the counter ion. [30][31][32] The ESI-MS/MS experiments were performed by collision induced decomposition (CID) of the free cations. As expected, the counter ion does not play a role in the fragmentations, hence the ESI-MS/MS spectra are reported by indicating only the cation species 1-4 ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The ESI and ESI-MS/MS mass spectra of two isomeric classes, oxadiazolyl-pyridinium salts, have been investigated. The ESI mass spectra [30][31][32] show, as well as the peaks due to cations M + , peaks corresponding to ion aggregates formed by two cations and the related anion [(M + ) 2 •Y -], that lead to the identification of the counter ion. The ESI-MS/ MS spectra obtained by CID of the free cations was able to distinguish between the isomeric of salts.…”
Section: Discussionmentioning
confidence: 99%